2021
DOI: 10.1002/mrm.28710
|View full text |Cite
|
Sign up to set email alerts
|

Joint image and field map estimation for multi‐echo hyperpolarized 13C metabolic imaging of the heart

Abstract: Image reconstruction of metabolic images from hyperpolarized 13 C multiecho data acquisition is sensitive to susceptibility-induced phase offsets, which are particularly challenging in the heart. A model-based framework for joint estimation of metabolite images and field map from echo shift-encoded data is proposed. Using simulations, it is demonstrated that correction of signal spilling due to incorrect decomposition of metabolites and geometrical distortions over a wide range of offresonance gradients is pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…Reed et al demonstrated improved B 0 shimming to mitigate the nonuniform circumferential HP [ 13 C]bicarbonate signal from the Myo 13 . Traechtler et al proposed a model‐based reconstruction to correct the B 0 ‐induced phase offsets in HP 13 C multi‐echo acquisition 12 . Considering the other contributing factors besides off‐resonance effect, direct measurements of in vivo T2 would further benefit the cardiac HP 13 C studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reed et al demonstrated improved B 0 shimming to mitigate the nonuniform circumferential HP [ 13 C]bicarbonate signal from the Myo 13 . Traechtler et al proposed a model‐based reconstruction to correct the B 0 ‐induced phase offsets in HP 13 C multi‐echo acquisition 12 . Considering the other contributing factors besides off‐resonance effect, direct measurements of in vivo T2 would further benefit the cardiac HP 13 C studies.…”
Section: Discussionmentioning
confidence: 99%
“…13 Traechtler et al proposed a model-based reconstruction to correct the B 0 -induced phase offsets in HP 13 C multi-echo acquisition. 12 Considering the other contributing factors besides off-resonance effect, direct measurements of in vivo T * 2 would further benefit the cardiac HP 13 C studies.…”
Section: S Of Hp 13 C Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, as T * 2 increases at lower field strengths, the available signal persists longer, which, together with the reduced spectral span of the metabolites at lower fields, can be utilized to adaptively change the acquisition bandwidth proportional to 𝜔, that is, BW ∝ 𝜔. For the field-dependent SNR scaling according to Equations ( 9) and (10)…”
Section: Bandwidth Adaptionmentioning
confidence: 99%
“…10,30 Reconstruction was performed in MATLAB using nonlinear conjugate gradient-based reconstruction with ground truth B 0 correction based on a measured 1 H field map, and total variation regularization with 𝜆 = 0.3. 10 Image SNR was calculated as the magnitude of the metabolite (m) image 𝝆 m over pixels v of each dynamic frame t d divided by the SD over all pixels from the last dynamic frame t noise (noise only) of the reconstruction without regularization ρm . Metabolic SNR time curves were extracted as the average signal over all pixels of the left ventricular blood pool (pyruvate and pyruvate hydrate) and myocardium (lactate, alanine, and bicarbonate), respectively (V ROI ):…”
Section: Hyperpolarized In Vivo Experimentsmentioning
confidence: 99%